Cure vs. Care: Case in Korea - Kim, Sung-Ho; Kwon, Ik-Whan G.; Kim, Hanjun (British Journal of Healthcare and Medical Research, 2026)
Medical sciences increase the life expectancy to the point that centenarian population is projected to quadruple over the next 30 years. Highlighting medical advancements and corresponding technological achievements is undeniably crucial for optimizing therapies and treatments; however, this focus significantly puts aside the critical goal of alleviating suffering in dying patients (Lionis et al., 2025), especially those in the end-of-life (EOL) stage. End-of-life is an emotional issue for everyone involved (patients, family, caregivers and religious community, etc.) which requires not only medical interventions, more importantly it (EOL) requires emotional support by and from every stakeholder in relieving pain and emotional stress emanated from isolation from family and friends, neglected by society and abandoned by government.